APPLICATION OF 4D TOMOGRAPHY DOUBLE-DIFFERENCE IN DEEP BLOCK CAVING UNDERGROUND MINES FOR CAVE PROPAGATION MONITORING - Mahasca Kusuma, Briliandika
The Deep Block Caving underground ore mining method has proven its efficiency in accessing deep ore reserves. While advantageous, this method poses challenges in monitoring mine safety and productivity. In this context, seismic 3odelling technology has been used to understand mine subsurface conditions. This activity must be monitored to avoid massive and uncontrolled rock damage, especially in the abutment zone and undercutting levels. This research was conducted in the Deep Block Caving underground mine and aims to monitor cave propagation using the Double-Difference passive seismic tomography method. This method is able to accurately relocate the location of the earthquake source and produce a local velocity structure near the earthquake source. Tomographic inversion was carried out in a time-lapse manner to obtain the velocity structure of each research data subset. The result is that there is a distribution of stress as the cave travels which is characterized by high velocity P and S due to compensation for changes in the low velocity values in the area in front of the cave which is starting to collapse. We also propose a significant change in the Vp/Vs ratio as an indicator of future caving. Therefore monitoring in mining areas is very important to prevent losses in the form of both life and material. To understand more about cave propagation, a comprehensive monitoring system has been designed and installed.